2018
DOI: 10.1145/3162616
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing 3D Floating Gate NAND Flash

Abstract: As both NAND flash memory manufacturers and users are turning their attentions from planar architecture towards three-dimensional (3D) architecture, it becomes critical and urgent to understand the characteristics of 3D NAND flash memory. These characteristics, especially those different from planar NAND flash, can significantly affect design choices of flash management techniques. In this article, we present a characterization study on the state-of-the-art 3D floating gate (FG) NAND flash memory through compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Ma [40] tested and analyzed the RBER(raw bit error rate) of 3D TLC NAND Flash and also proposed a life prediction scheme of 3D TLC NAND Flash based on RBER and SVM(support vector machine), the experiment results showed that the prediction scheme can significantly extend the lifetime of flash blocks. Q. Xiong et al [37] studied the delay and raw bit error rate of 3D NAND based on floating gate and they obtained similar results with 2D NAND. Toru [41] studied and analyzed the problems that should be paid attention to when developing the next generation of 3D NAND Flash from the perspective of power consumption, performance and reliability.…”
Section: Related Workmentioning
confidence: 77%
See 1 more Smart Citation
“…Ma [40] tested and analyzed the RBER(raw bit error rate) of 3D TLC NAND Flash and also proposed a life prediction scheme of 3D TLC NAND Flash based on RBER and SVM(support vector machine), the experiment results showed that the prediction scheme can significantly extend the lifetime of flash blocks. Q. Xiong et al [37] studied the delay and raw bit error rate of 3D NAND based on floating gate and they obtained similar results with 2D NAND. Toru [41] studied and analyzed the problems that should be paid attention to when developing the next generation of 3D NAND Flash from the perspective of power consumption, performance and reliability.…”
Section: Related Workmentioning
confidence: 77%
“…Venkatesan [36] discussed the fundamentals and electron properties of 3D NAND Flash from the view of fabrication process integration and equipment engineering. References [11,37,38] compared 2D NAND Flash and 3D NAND Flash in terms of physical structure and working principle, and analyzed the advantages and problems brought by 3D technology. Seo [39] studied the interference between flash cells in terms of the composition of 3D NAND Flash cells.…”
Section: Related Workmentioning
confidence: 99%
“…Chen et al [12] optimized the garbage collection performance in the view of block erase efficiency and proposed a multi-block erase strategy. Xiong et al [29] and Wu et al [30] studied the characteristics and challenges of 3D flash memories with the floating-gate (FG) type and the charge-trap (CT) type, respectively. Hung et al [31] studied the cross-layer process variation problems of 3D vertical-gate flash and proposed three layer-aware program-andread scheme to reduce P/E cycle numbers and to improve read performance.…”
Section: Related Workmentioning
confidence: 99%
“…Two recent works compare the retention loss phenomenon between 3D NAND and planar NAND flash memory [65,70] through real device characterization, and report findings similar to our work regarding the early retention loss phenomenon. Two other recent works use a methodology similar to ours to characterize 3D NAND devices based on different 3D NAND flash memory cell technologies (i.e., 3D floating-gate cell and 3D vertical gate cell) [38,94,95], which are less common than the 3D charge trap NAND flash memory cell technology that we test in this paper. Other recent works [23,31,78,80,92] report several differences of 3D NAND flash memory from planar NAND flash memory.…”
Section: Related Workmentioning
confidence: 99%